2015
DOI: 10.1080/02640414.2015.1055292
|View full text |Cite
|
Sign up to set email alerts
|

Position-specific performance indicators that discriminate between successful and unsuccessful teams in elite women’s indoor field hockey: implications for coaching

Abstract: The aim of this investigation was to establish median performance profiles for the six playing positions in elite women's indoor hockey and then identify whether these position-specific profiles could discriminate between qualifying (top four), mid-table should build from these data to examine dribbling, pressing and patterns of play when outletting.3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 17 publications
0
7
0
3
Order By: Relevance
“…In field hockey, higher possession rates may be more related to frequently losing control of the ball to the opponent, since rates of creating opportunities are low. Findings for field hockey corroborate the importance atributed to the preparatory actions to a shot [ 47 ], with emphasis to passing and interception-related actions [ 48 ].…”
Section: Discussionmentioning
confidence: 65%
“…In field hockey, higher possession rates may be more related to frequently losing control of the ball to the opponent, since rates of creating opportunities are low. Findings for field hockey corroborate the importance atributed to the preparatory actions to a shot [ 47 ], with emphasis to passing and interception-related actions [ 48 ].…”
Section: Discussionmentioning
confidence: 65%
“…10 The study on field hockey compared the differences in pass and interception among qualifying teams, mid-table teams and relegated teams. 11 Research into professional basketball showed that the performance characteristics of the team will change when facing different levels of opponents. 12 Recently, studies evaluated the influence of contextual factors and time on playing styles in professional soccer, and found that teams play more aggressively at home, and their offensive actions increase as the season progresses.…”
Section: Introductionmentioning
confidence: 99%
“…In this status, each of the two players repeats the execution of attacking/avoiding actions at every moment; therefore, the status continuously fluctuates until the game is over (Yamamoto et al, 2013 ; Okumura et al, 2017 ). Similar to expert 1-on-1 combat game players, expert soccer teams frequently thread the pass, and thus, the ball is less likely to be intercepted by the opponent compared to in games with less-skilled teams (Dellal et al, 2011 ; Vinson and Peters, 2016 ). At first sight, a system structured by the collective behavior of the two teams in the game seems to freeze with any fluctuation; however, the frequency of within-team pass exchanges is rather higher in expert games than in games performed by less-skilled players.…”
Section: Introductionmentioning
confidence: 99%